Toxic reaction to inhaled paint fumes. Issue 766 (August 1989) - Atkinson, L.; Ince, P.; Smith, N. M.; Taylor, R.
Abstract : An acute confusional state was observed to follow heavy exposure to polyurethane gloss paint fumes in a previously healthy 60 year old man. This state remitted over a 3-day period, but was followed by transient bone marrow suppression and evidence of liver cell damage. The corroborated absence of other toxins and the temporal association of exposure to paint fumes suggest that a volatile paint component was responsible. White spirit is the major volatile solvent in polyurethane gloss paint. Ingestion of related aliphatic hydrocarbons has been reported to cause nausea, drowsiness and hepatotoxicity, but these symptoms have not previously been documented following excessive inadvertent inhalation of paint fumes.